Impact of a Patient Blood Management Program and an Outpatient Anemia Management Protocol on Red Cell Transfusions in Oncology Inpatients and Outpatients - Gross, Irwin (Oncologist, 2016)
BACKGROUND. Patient blood management (PBM) programs are associated with reduced transfusion usage, reduced hospital costs, and improved patient outcomes. The application of PBM principles in patients with malignant disease might achieve similar results. However, this population presents unique challenges. The aim of the present study was to investigate the impact of a PBM program on blood usage and patient outcomes in cancer patients, particularly in the setting of restricted use of erythropoiesis-stimulating agents (ESAs). MATERIALS AND METHODS. A retrospective observational study was performed of patients admitted with a primary diagnosis of malignancy treated at Eastern Maine Medical Center as inpatients or outpatients, or both, from January 2008 through July 2013. RESULTS. The proportion of inpatients and outpatients receiving ESAs decreased from 2.9% in 2008 to 1.1% in 2013 (p < .001). During the same period, an increase occurred in the mean dose of intravenous (IV) iron from 447 mg (95% confidence interval [CI], 337–556) to 588 mg (95% CI, 458–718). The mean red blood cell (RBC) units transfused per inpatient and outpatient episode decreased from 0.067 to 0.038 unit (p < .001). In inpatients, significant increases occurred in the proportion of single-unit RBC transfusions (p < .001) and patients infused with IV iron (p = .02), and significant decreases in the mean pretransfusion hemoglobin (p = .02) and RBC transfusion rate (p = .04). In-hospital mortality and length of stay did not change significantly during this period. CONCLUSION. Despite the decreased use of ESA therapy, the implementation of a PBM program and outpatient anemia management protocol in cancer patients at our medical center was associated with significant reductions in RBC usage. IMPLICATIONS FOR PRACTICE: Published data have shown that patient blood management results in a significant reduction in transfusion rates with similar or improved clinical outcomes across a spectrum of medical and surgical patients. However, limited data are available in oncology. The present study has shown that a strategy of ordering red blood cells one unit at a time, a conservative (restrictive) transfusion hemoglobin threshold, and increased use of intravenous iron to manage anemia can result in a significant decrease in transfusion exposure. This reduction is possible despite reduced erythropoiesis-stimulating agent (ESA) usage as a result of a Food and Drug Administration-boxed warning and Centers for Medicaid and Medicare Services reimbursement restrictions to the use of ESAs in hematology and oncology.